Peningkatan Hasil Belajar PKN dengan Metode Pembelajaran Index Card Match di SDN 004 Samarinda Ilir (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study aims to improve the learning outcomes of Civic Education (PKn) in grade III students of SDN 004 Samarinda Ilir through the application of the Index Card Match learning method. This method involves the activity of looking for pairs of cards that function to repeat the learning material that has been taught previously. This approach aims to improve understanding of the concepts taught and create an active and fun learning atmosphere. In its implementation, students work together to find suitable card pairs, which can improve interaction between students and activate the learning atmosphere. This type of research is Classroom Action Research (PTK) which is carried out in three cycles in grade III B SDN 004 Samarinda Ilir with 31 students as research subjects. The data collection techniques used include observation sheets, learning outcome tests, and documentation. The results of the study show that the application of the Index Card Match method can significantly improve student activities and learning outcomes. In the first cycle, student activity reached 72.58%, in the second cycle it increased to 84.47%, and in the third cycle it reached 90.12%. The average student score also increased from 61.45 in the pre-cycle to 90.32 in the third cycle, with learning completeness reaching 96.78%, which has met the Minimum Completeness Criteria (KKM). Based on these results, it can be concluded that the Index Card Match method is effective in improving students' PKn learning outcomes.